Efficacy of freeze-dried platelet-rich plasma in bone engineering. (January 2017) - Nakatani, Yuya; Agata, Hideki; Sumita, Yoshinori; Koga, Takamitsu; Asahina, Izumi
Highlights: This article describes the study about bone engineering using freeze-dried PRP. Freshly isolated PRP can be stored without functional loss by freeze-drying. Concentrated PRP is produced by decreasing the amount of water for rehydration. The concentration of PRP may enhance its efficacy in bone engineering. Abstract: Objective: Platelet-rich plasma (PRP) is typically isolated and applied immediately after preparation, making it both a time- and labor-intensive addition to the operative procedure. Thus, it would be convenient if PRP could be preserved. We evaluated the efficacy of freeze-dried PRP (FD-PRP), as compared with freshly isolated PRP (f-PRP) for bone engineering. Design: FD-PRP was prepared by lyophilization of f-PRP and was subsequently preserved at −20 °C for one month. It was then rehydrated with an equal or 1/3 amount of distilled water (×1FD-PRP, ×3FD-PRP, respectively), and we assessed its gelation properties and the release of growth factors (PDGF-BB, TGF-β1, and VEGF). We also examined the bone forming ability with onlay-grafting on mice calvaria using β-TCP granules as a scaffold. Results: FD-PRP showed comparable gelation as f-PRP. In terms of growth factor release, × 1FD-PRP released identical concentrations of PDGF-BB and TGF-β1 to f-PRP, while ×3FD-PRP released approximately 3-fold concentrations when compared with f-PRP. In vivo, ×1FD-PRP promoted identical levels of the bone formation as f-PRP, and ×3FD-PRP induced more abundant bone formation. Conclusions: These results suggest that f-PRP can be stored without functional loss by freeze-drying and the concentration of PRP may improve its efficacy in bone engineering.